Pemberdayaan Kelompok Masyarakat Dalam Pengemasan Paket Wisata Pedesaan Di Desa Pelaga Kecamatan Petang Kabupaten Badung - Desak Gede Sri Intan Wahyuni; I Putu Anom (JURNAL DESTINASI PARIWISATA, 2018)
In Indonesia there are various kinds of tourism activities where one of them from the alternative tourism is rural tourism. When the rural tourism began to be developed then the community must also participate to play an active role in the development of rural tourism. Therefore, the empowerment of local people in this rural tourism activity is very important. The focus of this research is to know the form of community empowerment, the process of community empowerment, the components of the package of rural tour packages, the forms of tour packages offered, and the distribution channel. This research method using qualitative descriptive method. The process of collecting data is done by observation, interview and literature study. The data are then grouped, described, analyzed, then summarized. The findings of research results from community empowerment in packing of rural tourism package include: 1) The form of empowerment of community groups in Pelaga Village is the Sadar Wisata Group, 2) The empowerment of community groups in packing of rural tour packages includes components of rural tour package, Tour packages offered, and distribution channels. From this research, it can be concluded that the empowerment of community groups in packing rural tourism packages related to the many potentials that have the need for socialization and counseling to Pelaga Village community groups to be directly involved in tourism activities. Sustainability of empowerment activities can be developed and improved again because the better the empowerment activities are held to eat the better the benefits obtained by the community. Keywords:Empowerment, Packaging, Tour packages